Textbook of Clinical Electrocardiography - Chugh, S. N. (Jaypee Brothers Medical Publishers, 2006)
The basic aim of this book remains unchanged, namely to describe the text extensively followed by ECG illustrations. The introduction of colour throughout the book has provided an additional opportunity to beautify the tables and figures as well as making increased use of coloured photographs. The book is intended for the postgraduate students and clinicians for clinical practice. It is also useful for the students who intend to pursue further study in cardiology.